The implementation of the "Selamatan Petik Pari" tradition carried out by the people of Petungsewu Village, Wagir District, Malang Regency - Maran, Maria Dolorosa Jawa; Kusufa, Roni Alim Ba’diya (Journal of Socio-Cultural Sustainability and Resilience, 2024)
Background: Petungsewu Village, located in Wagir District, Malang Regency, is a village rich in culture and tradition. One tradition that is still preserved to this day is Selamatan Petik Pari, a traditional ceremony performed by the local community as a form of respect to Dewi Sri, the goddess of rice who is believed to be the protector of rice plants. This tradition reflects the beliefs and values passed down from generation to generation, demonstrating the Javanese people's spiritual and mystical connection with nature and their ancestors. Method: This research uses a qualitative approach, naturalistic or interpretive, focusing on interpreting data collected in natural settings. It is descriptive, aiming to understand and describe phenomena such as behaviour, perception, and motivation within their natural context. Findings: Selamatan Petik Pari involves various rituals rich in symbolism, such as the preparation of tumpeng and takir containing a full meal, as well as incantations and prayers adapted to the religious beliefs of the majority of the population, namely Islam. This tradition not only aims to ask for a bountiful harvest and protection from pests, but also as a means to strengthen social relations among residents and between residents and the village government. The village government, represented by the village head and village officials, shows active participation and support for the implementation of this tradition. They hope that this tradition can continue to be preserved and passed on to the younger generation, thus not only strengthening cultural identity but also strengthening familial and communal relations among the community. Conclusion: Selamatan Petik Pari in Petungsewu Village is not only an agricultural tradition, but also an important means of maintaining and developing cultural values, social togetherness, and harmony between humans and nature. This tradition emphasises the importance of preserving cultural heritage as part of national identity and as a tool to answer social challenges in the present. Novelty/Originality of this article: The model in this study can be applied in various regions to promote cultural heritage, improve local economies, and encourage community participation in sustainable development.